Sosialisasi Manajemen Wakaf di PWNU Jawa Barat - Jalaluddin, Jalaluddin; Furqon, Muhamad (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2025)
This community service activity addresses the issue of under-optimized waqf management in PWNU West Java, despite its significant potential to support economic growth and community welfare. The main issues include a lack of public understanding of productive waqf, limited application of technology in waqf management, and an inadequate regulatory framework. The activity uses Participatory Action Research (PAR) method, involving participants in interactive discussions, material delivery, and evaluation. The workshop was held at the PWNU West Java Office, aiming to enhance participants' understanding of Islamic economic principles, productive waqf management, and the use of digital technology in waqf management. The results showed an increase in participants' understanding of Islamic economics and waqf concepts, as well as the importance of digital technology in improving efficiency and transparency. Additionally, the discussion resulted in recommendations, such as the establishment of a digital-based waqf management unit and enhanced collaboration with Islamic financial institutions. This activity is expected to strengthen waqf management in Indonesia and promote inclusive Islamic economic development.